Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan PT. Permodalan Nasional Madani Di Kecamatan Sekotong - Heni Widiawati; Nizar Hamdi; Khaerul Hadi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This research aims to examine the factors that influence the performance of PT employees. Madani National Capital in Sekotong sub-district. So that the variables in this study consisted of 2 (two) independent variables namely Training (X1), Motivation (X2) and the dependent variable Performance (Y). The population of this research is all employees of PT. PNM in Sekotong sub-district. The total sample was 33 respondents, samples were taken using non-probability sampling techniques. Data was obtained by distributing questionnaires to all employees of PT. PNM online via the WhatsApp application with the Google Form link and conduct interviews. Data were analyzed using Multiple Linear Regression Analysis. The results of this study indicate that training has a partially significant effect on performance and motivation has a partially significant effect on performance. So it can be concluded that the training and motivation variables simultaneously have a significant effect on performance. Meanwhile, the motivation variable has the most dominant influence on performance. The results of this study also show that the independent variables (Training and Motivation) are able to explain the dependent variable (Performance) as much as 78.7%. Meanwhile, the remaining 21.3% is influenced by other variables outside the variables of this research.